(untitled) (Academic Journal of Internal Affairs, 2012)
Building on recent constitutional, judicial and legislative developments, the author provides an assessment of where the limits of self defense can be drawn (in light of the case of the Constitutional Court) and to what degree are individuals obliged to evade and escape from unlawful threats and attacks.